Relative tolerance of wheat cuItivars to leaf rust and components responsible for yield losses - and K.D. SRIVASTAVA, K.V.S. MEENAKUMARI, D.V. SINGH (Indian Phytopathology, 2002)
The effect of leaf rust (Puccinia recondita tritici) revealed that in the susceptible wheat cultivars Lal Bahadur, Kalyansona and WL 711, the disease progressed non-logarithmically and attained higher A-values, indicating fast rusting. These cultivars suffered more yield losses than moderately resistant Arjun, Raj 1555, HD 2285 and HD 2329 which remained in logarithimic phase throughout the course of epidemic growth, exhibiting slow rusting tendency. Wheat cultivars, C 306, Sonalika, Lok I and WH 147 remained initially in logarithmic pha e and thereafter moved to non-logarithmic phase. These cultivars had relatively higher A-value but suffered less reduction in yield, possibly due to tolerance mechanism. The yield components, viz., number of grains, earhead length and 1000-grain weight were responsible for reduction in yield due to leaf rust. In case of Lal Bahadur, Kalyansona and WL 711, the losses were due to fewer grains and reduction in grain weight whereas. C 306 suffered mainly on account of loss in number of grains. The loss in yield of Lok I, Sonalika and WL 147 was due to lower grain weight.